Z problematyki prawnej rejestrów związanych z realizacją Wspólnej Polityki Rolnej - Jeżyńska, Beata (Wydawnictwo Naukowe UAM, 2008)
The main aim of the paper is to assess the effects of registers and to determine their function in the sphere of agricultural production under quotas or limitations. Production limitation requires that both public and non-public registers are kept. The main function of public registers is the creation of legal effects for producers and operators participating in a regime of common marker organisation under quotas as the entry into registers constitutes a legal prerequisite for the operators to gain access to instruments of CMO. The registers play also a selective role among economic entities by giving only to some of them a special status resulting from the fact that production quotas have been assigned to them. Non-public registers provide for an extensive set of data which allows for an assessment of the economic situation of registered producers, particularly with regard to the level of quota utilisation. Registers of agricultural producers functioning in the limited production regime are usually kept at various public administration agencies, dispersed, however, among public bodies and other market players. The variety of bodies administering particular registers confirms the conclusion that there is no tendency or even intention to combine or integrate those registers, or. at least, to subject them to one common registration procedure. And yet, the nature of production quotas is such that the registering obligations could be simplified and unified. This would limit their scope and consequently improve the smooth functioning of the market. Further, the transparency of market instruments would improve the process o f their supervision and would facilitate market assessment.

L’obiettivo dell'articolo e soprattutto quello di valutare gli effetti della registrazione e di determinare le funzioni dei registri condotti per la produzione agricola sottoposta alle limitazioni quantitative. Per tali produzioni vengono utilizzati due tipi di registri: pubblici e non-pubblici. La funzione principale dei registri pubblici e quella legislativa che si riconduce al collegamento dell'effetto della registrazione all’ammissione del soggetto registrato ai meccanismi dell’organizzazione comune di mercato del prodotto limitato. I registri pubblici realizzano anche la fiinzione selettiva che consiste n e ll’attribuizione ai soggetti leggittimati alle quote produttive uno status particolare economico. I registri non-pubbblici creano invece ampie banche dati che permettono la valutazione della situazione economica dei produttori registrati e soprattutto dello stato di utilizzazione dei limiti produttivi concessi. I registri agricoli ftinzionanti nell’ambito del regime delle produzioni limitate sono di solito registri amministrativi tenuti da diversi livelli delle pubbliche amministrazioni e degli altri soggetti del mercato. Una tale varieta rende chiaro il fatto che nell'ambito della registrazione della produzione limitata non emergono tendenze di integrazione e di unificazione dei registri o almeno di unificazione delle relative regole. Tuttavia, prendendo in considerazione il carattere delle quote di produzione e la loro funzione di razionamento gli obblighi legati alia registrazione si possono e si devono semplificare. La semplificazione permettera di limitare il loro ambito e, di conseguenza, di rendere piu effettivo il fiinzionamento del mercato. Grazie alia semplificazione verra migliorata anche la trasparenza degli strumenti di mercato vigenti, il controllo sul loro utilizzo e la valutazione dello stato di andamento del mercato.
Registers and the implementation of common agricultural policy - legal issues
La problematica dei registri legati all'attuazione della politica agricola comune